Comparison of the effects of preoperative and intraoperative intravenous application of dexketoprofen on postoperative analgesia in septorhinoplasty patients: randomised double blind clinical trial. - Ozer, A.B.; Erhan, O.L.; Keles, E.; Demirel, I.; Bestas, A.; Gunduz, G. (My University, 2012)
Postoperative analgesia is important because it prevents the adverse effects of pain. To study the effect of preoperative or intraoperative application of dexketoprofen on postoperative analgesia and patient comfort in patients undergoing septorhinoplasty. A randomized, double-blind, placebo-controlled study. The study included 100 patients randomly assigned to four groups. Patients from group 50/0 got 50 mg dexketoprofen 30 minutes prior to the operation; patients from group 0/50 got 50 mg dexketoprofen 30 minutes after the operation, and patients from group 25/25 got 25 mg dexketoprofen both 30 minutes prior and 30 minutes after the operation. Dexketoprofen was not applied to any of the patients from group C. Once in the recovery room, patient-controlled analgesia was received to all patients. The patients' visual analog scale (VAS), sedation, nausea and vomiting and dyspepsia complaints were recorded at 1, 2, 3, 4, 5, 6, 7, 8, 12 and 24 hours. In addition, patient satisfaction, intraoperative fentanyl and consumption of tramadol in the postoperative 24 hour period were recorded. The VAS, nausea and vomiting, sedation and patient satisfaction scores were lower in patients from all groups that had received dexketoprofen compared to the controls. There was no difference in intraoperative fentanyl consumption between the groups. The consumption of tramadol was significantly higher in group C compared to all other groups. Dexketoprofen provides good postoperative analgesia and patient satisfaction if applied intravenously to septorhinoplasty patients. However, there is no significant difference between preoperative and intraoperative applications of dexketoprofen.
Keywords: Adult; Anti-Inflammatory Agents, Non-Steroidal; Double-Blind Method; Female; Humans; Infusions, Intravenous; Ketoprofen; Male; Nasal Septum; Pain, Postoperative; Rhinoplasty; drug derivative; ketoprofen; nonsteroid antiinflammatory agent; adult; article; comparative study; controlled clinical trial; controlled study; double blind procedure; female; human; intravenous drug administration; male; methodology; nose reconstruction; nose septum; postoperative pain; randomized controlled trial